Gig Economy in the Digital Age: Task Clarity, Technology Access, Social Support, Motivation, and Impact on Worker Performance - Putri Ayu Permata Devi; Bambang Purwanto; Yuliati; Wulan, Titis Sri (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
The rapid growth of the gig economy in Indonesia has transformed the nature of digital work, offering flexibility yet creating challenges related to job security and performance. This study aims to analyze the influence of task clarity, technology access, social support, and motivation on the performance of gig workers in Indonesia. A quantitative descriptive approach was used by distributing online questionnaires to 300 digital platform workers across the Greater Jakarta area. Data were analyzed using multiple linear regression after meeting the requirements of validity, reliability, and classical assumption tests. The results show that social support and motivation have a significant positive effect on performance, while task clarity and technology access show a positive but insignificant relationship. The findings indicate that psychosocial factors contribute more strongly to gig workers’ performance than structural or technical aspects. These results imply that maintaining social connections and intrinsic motivation is crucial for sustaining productivity in flexible digital work environments. This study is limited to respondents in urban areas and does not include qualitative insights from workers’ lived experiences. Future research is suggested to expand the sample across regions and integrate qualitative analysis to better understand the dynamics of digital labor in Indonesia.